Miranda: ustavna pravica ali ne? - Čibej, Zarja (Revus (Ljubljana), 2005)
The author analyzes and discusses the development of the American miranda from 1966 until today and compares it with the Slovene miranda. She argues that the main difference between them is in the conditions under which miranda applies and in the constitutional protection each of them is afforded. The American miranda applies when a suspect is taken into custody and she is interrogated, while the Slovene miranda applies if a suspect is either taken into custody or she is interrogated by the police. In the former case miranda is protected by the Slovene Constitution, but not in the latter. Through the analysis of the jurisprudence of the US Supreme Court the author demonstrates that the American regulation of miranda has become very close to what is considered to be the continental approach to the criminal procedure in the last few years, since the US Supreme Court, in the name of finding the material truth at trials has recognized numerous exceptions to miranda. The latest exception to miranda allows for the state at a trial to introduce the physical evidence derived from a statement of the defendant who had not been given the miranda warnings. The author argues that the American miranda with the applicable exceptions is very similar to the miranda of the Slovene Criminal Procedure Act that allows for the police interrogation without the presence of an attorney, which is evidenced "only" by the official note, which is not regarded as a formal evidence, but on the basis of which the police may lawfully seek other evidence and which the trial judge is free to review. The author emphasizes the difference between the Slovene and the American constitutional provisions related to miranda, especially in the view of the nature of the protection that each provides for the miranda rights. Since the American Constitution has no explicit provisions regarding the right to remain silent and the right to the assistance of an attorney, miranda is only one of the ways to safeguard the privilege against self-incrimination. Therefore, miranda itself is not a constitutional right and a violation of miranda without more does not justify the exclusion of an evidence obtained in the violation of miranda. The Slovene Constitution, on the other hand, has explicit provisions concerning the right to remain silent and the right to the assistance of an attorney in cases where the freedom to move is restricted in a significant way, therefore the Slovenian miranda in cases where the suspect is taken into custody is not only a way of safeguarding the privilege against self-incrimination, but a constitutionally protected right. The author argues that precisely for this reason, the regulation of the police interrogation in cases where a suspect is taken into custody and is not afforded the assistance of an attorney is not in accordance with the provisions of the Slovene Constitution. In cases like that the evidence derived from such official note should be excluded as well as the official note itself, since it was obtained in a way that directly violates the constitutional provisions with respect to the right to the assistance of an attorney.
Keywords: dokazi; kazenski postopek; odvzem prostosti; policijsko zasliševanje; pravica do molka; pravica do zagovornika; predkazenski postopek; Slovenija; ZDA